Profiles of Burnout, Coping Strategies and Depressive Symptomatology - Martínez, Juan Pedro; Méndez, Inmaculada; Ruiz-Esteban, Cecilia; Fernández-Sogorb, Aitana; García-Fernández, José Manuel (Frontiers in Psychology, 2020)
Burnout syndrome is has been associated with mental health problems such as depression, anxiety, and stress. Given this fact, some teachers implement various coping strategies for emotional control that are not always functional to mitigate such difficulties. Accordingly, this study aimed to identify different burnout profiles that vary in the levels of the three underlying dimensions: depersonalization, emotional exhaustion, and personal accomplishment. Further, this study aimed to examine whether there are significant differences in depressive symptomatology, coping strategies, and the quality of interpersonal relationships at school between teachers with varying burnout profiles. The Maslach Burnout Inventory, Zung Self-Rating Depression Scale, Coping with Stress Questionnaire, and a questionnaire that measured sociodemographic characteristics were administered to 215 teachers (men: 42.8 %) who were recruited from various secondary schools. Cluster analysis identified three different burnout profiles: groups of teachers with a predominance of (a) low levels of emotional exhaustion and high levels of personal accomplishment, (b) high levels of emotional exhaustion and depersonalization, and (c) low levels of depersonalization and personal accomplishment. The results revealed that there were significant differences in coping strategies, depressive symptomatology, and the quality of interpersonal relationships at school between teachers with different burnout profiles. These results have important implications for educational professionals. Specifically, the findings underscore the need for prevention and intervention programs that enhance teachers’ emotional skills, especially their ability to cope with exhaustion. These skills will alleviate their depression and consequently offer both teachers and students a conducive learning environment.